Membangun Sistem Pengawasan PPIU yang Efektif: Kebijakan untuk Meningkatkan Kepercayaan dan Kualitas Layanan Umrah - Tahir, Muh. (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy paper outlines the main issue faced in the implementation of umrah pilgrimage trips, which is the weak supervision of the operational activities of Umrah Travel Agencies (PPIU), posing high risks to service quality, unclear departure schedules, and low transparency. The main objective of this policy is to provide recommendations to strengthen the supervision of PPIUs through the enhancement of existing regulations, as well as to improve transparency and accountability in PPIU operations. The methodology used in this study is a qualitative approach with in-depth analysis of policies and case studies of various incidents that have occurred in the industry. The analysis results show that weak monitoring systems, lack of financial transparency in PPIUs, and insufficient regulations governing PPIU operations are the primary causes of these problems. In general, the proposed policy involves strengthening supervision, establishing service quality standards, and implementing strict certification for PPIUs. Thus, the author concludes that this policy plays an important role in improving the supervision system and enhancing the quality of PPIU services, ensuring better protection for Umrah pilgrims. The author recommends that the Ministry of Religious Affairs immediately issue regulations concerning the Standards of Quality and Supervision for Umrah Travel Agencies (PPIU).